IMPLEMENTASI MANAJEMEN PERPUSTAKAAN DI SMK BINA RAHAYU DEPOK - Panesa, Aprilia; Rahayu, Arafah Mutia; Mulkiyah, Jahrotul; Sujud, Lia Atsari (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of library management at SMK Bina Rahayu Depok. Using a qualitative approach and case study methodology, the research investigates various aspects of library management, including book collection management, member services, the use of information technology in the library system, and overall library performance evaluation. Data were collected through direct observation, in-depth interviews with librarians and teachers, and internal documentation. The findings reveal that library management at SMK Bina Rahayu Depok has demonstrated systematic efforts to improve service quality and resource management. However, several challenges remain, such as budget constraints, insufficient staff training in technology, and low student engagement in library activities. This study provides key recommendations to strengthen library management through enhanced human resources, integration of digital systems, and fostering a reading culture within the school environment. The findings contribute to a deeper understanding of the challenges and opportunities in managing libraries in vocational high schools in Indonesia.